أهمية استخدام البرمجة الخطية في المصانع ودورها في تحسين معدلات أدائها (Journal of Humanitarian and Applied Sciences, 2023)
This research deals with explaining the process of using linear programming as one of the methods of operations research to reach the optimal solution from among the possible solutions that help the factory management in taking the appropriate decision to raise production returns to the maximum possible extent or reduce costs to the lowest possible degree, and this is only done by using one The quantitative methods and the best methods in this research is the method of linear programming, and in this research I dealt with introducing some concepts of linear programming and making an applied example of using linear programming in reaching the optimal solution in the case of the problem, which is to find the largest possible return among the available returns, and the results were discussed Which has been reached, which is a set of available alternatives and testing the best alternative among these alternatives, and deducing some concepts resulting in the use of linear programming in factories, as well as the commandments to reach the correct decision of production capacity in order to achieve the highest return among the possible returns at the lowest possible cost.
Keywords: Programming; Linearity; Production; Optimization; Corner